INFECTIOUS DISEASES, FACTORS THAT SPREAD THEM (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Infectious disease, in medicine, a process caused by an agent, often a type of microorganism, that impairs a person’s health. In many cases, infectious disease can be spread from person to person, either directly (e.g., via skin contact) or indirectly (e.g., via contaminated food or water).